Erfahrungen mit dem Höhentraining bei Laufdisziplinen - Popov, I. (1996)
The dissertation is based on research data and author's experience from about 40 training camps at high altitude. Subjects were middle- and long distance runners. The effects of altitude hypoxia on the organism of athletes and on the sport performances were studied. Attention was paid to the individual's adaptability to hypoxia and to altitude experience. The research data and the author's experience accumulated through the years suggest that altitude training may have a positive effect on sport performances of distance runners. It may be practiced in every training period, but training methods have to be adapted accordingly. The altitude hypoxia imposes some limitations on the intensity of continuos exercises. Prolonged rest intervals are needed during interval training sessions and along the microcycles. The positive effects of altitude training are most significant if the terms of competitions are in accordance with the phases of reacclimatization. The optimal extent of the altitude training camps, aiming for competitions at sea level, is from 3 to 4 weeks ('classically' - 3 weeks). They are mostly applied during the preparative period(s) of the years-macrocycle, but there are positive experiences with shorter (6 - 12 days) camps as well. They might be very useful as a means of active rehabilitation and psychological relaxation after a series of strenous training microcycles or competitions along the training year. The altitude training, of course, is not penacea for all problems of contemporary endurance training, but it might be a means of preference for endurance enhancement in middle and long distance runners.